Հայատառ թուրքերեն, թաթարերեն, ղփչաղերեն, քրդերեն և հունարեն գրականությունների մասին - Ստեփանյան, Հասմիկ (Ասողիկ հրատ.)
There is very little number of Greek manuscripts with Armenian aiphabet.They are prayers, songs, and word-lists generally of the 15-19th centuries that had only practical meaning. The Kurdish literature in Armenian characters has been created with an aim to make Kurds literate. There are prayers, dictionaries, songs and examples from folklore that represent ethnographic importance. In the age of Publishing Armenian authors developed textbooks, alphabets and dictionaries of Kurdish and Armenian languages. The Bible, the Gospels, theological books were translated and published in the period of activities of various American and European missionaries. The Tatar and Kipchak literature with Armenian aiphabet has some historical and philological value. It is aversion of Turkish literature in Armenian characters and has been developed in 13-14th centuries.
Keywords: Գրականություն; Պատմություն